CowComfort: A R-shiny app to visualize the evolution of thermal comfort of dairy cows under climate change and the associated uncertainty - Anne-Isabelle Graux; Thomas Demarty; Philippe Faverdin (SoftwareX)
We present CowComfort, an R-shiny app developed to assist researchers, stakeholders and policy makers in the spatialized visualization of the evolution of the thermal comfort of dairy cows under climate change. The application is designed to take into account the uncertainty associated with the climatic projection and the calculation of the thermal indices. This app and its associated data can be used in modelling research and to communicate about the impact of climate change on dairy cows and the required adaptations. An illustration is given for French climatic data and for an evaluation of the thermal stress based on several calculations of the temperature humidity index. It can be easily repeated and extended to other climate situations and thermal stress evaluations.